2014
DOI: 10.1111/syen.12052
|View full text |Cite
|
Sign up to set email alerts
|

Current status of the systematics and evolutionary biology of Grylloblattidae (Grylloblattodea)

Abstract: This year marks a century since the description of Grylloblatta campodeiformis Walker (1914) and the enigmatic insect family Grylloblattidae (Grylloblattodea 1 ). In the past decade, our understanding of the evolutionary diversification of grylloblattids has grown, giving prospect to elaborating other aspects of their biology, in particular their ecology, physiology and behaviour. Specific accomplishments include clarification and extension of grylloblattid geographic distributions (Schoville,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…Galloisiana paraphyletic and suggesting this may be an undescribed genus (Schoville, 2014). There is, however, disagreement about the placement of this lineage as sister to Grylloblattella + Grylloblatta (Figure 1), or sister to Galloisiana + Grylloblattina (Figure 2; Figure S2).…”
Section: Evolutionary Diversification Of Mantophasmatodea and Gryllmentioning
confidence: 99%
“…Galloisiana paraphyletic and suggesting this may be an undescribed genus (Schoville, 2014). There is, however, disagreement about the placement of this lineage as sister to Grylloblattella + Grylloblatta (Figure 1), or sister to Galloisiana + Grylloblattina (Figure 2; Figure S2).…”
Section: Evolutionary Diversification Of Mantophasmatodea and Gryllmentioning
confidence: 99%
“…Grylloblattids (Insecta: Grylloblattodea: Grylloblattidae) are montane insects (see Fig. ) that inhabit parts of eastern Asia, the United States, and Canada (Schoville, ). Species in the genus Grylloblatta Walker (), commonly called ‘ice crawlers’, are confined to western North America where they are found associated with snow in alpine talus fields, or at low elevations in caves and lava tubes that retain seasonal ice (Kamp, ; Schoville & Graening, ).…”
Section: Introductionmentioning
confidence: 99%
“…Ice crawlers prefer to forage at cold temperatures (near 0°C), and have a narrow thermal tolerance that is highly conserved across lineages (Schoville et al ., ). Due to their rarity in museum collections, and the lack of adult males for descriptive taxonomy, species descriptions have been slow (Schoville, ). However, genetic studies have found that there are many locally endemic, undescribed Grylloblatta lineages, which are recognizable based on high levels of genetic divergence and reciprocal monophyly (Jarvis & Whiting, ; Schoville & Roderick, ; Marshall & Lytle, ).…”
Section: Introductionmentioning
confidence: 99%
“…When mentioning 'Grylloblattidae' we refer to the crown-group only (of which only extant species are known at present; Schoville, 2014). The traditional Linnaean nomenclature will be used herein; this does not imply the consent of OB to all aspects of this procedure.…”
Section: Nomenclatural Conventionsmentioning
confidence: 99%